What the Students for Fair Admissions Cases Reveal about Racial Preferences - Peter Arcidiacono; Josh Kinsler; Tyler Ransom (Institute of Labor Economics (IZA), 2022)
Using detailed admissions data made public in the SFFA v. Harvard and SFFA v. UNC cases, we examine how racial preferences for under-represented minorities (URMs) affect their admissions to Harvard and UNC-Chapel Hill. At Harvard, the admit rates for typical African American applicants are on average over four times larger than if they had been treated as white. For typical Hispanic applicants the increase is 2.4 times. At UNC, preferences vary substantially by whether the applicant is in-state or out-of-state. For in-state applicants, racial preferences result in an over 70% increase in the African American admit rate. For out-of-state applicants, the increase is more than tenfold. Both universities provide larger racial preferences to URMs from higher socioeconomic backgrounds.
Keywords: I23; I24; J15; 330; higher education; college admissions; affirmative action